2020
DOI: 10.1108/sampj-11-2019-0405
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability efforts in the fast fashion industry: consumer perception, trust and purchase intention

Abstract: Purpose This study aims to test for factors affecting environmental sustainability and purchase intention in the fashion industry. Accordingly, the authors developed a framework that depicts the relationships between perceptions of social responsibility, consumer attitude, trust, purchase intention and perceived consumer effectiveness. Design/methodology/approach An online survey was conducted with an internationally diverse sample of 216 consumers. Data were analysed using partial least squares structural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 56 publications
(169 reference statements)
3
34
0
2
Order By: Relevance
“…The authors found a review in other studies related to the Intention (INT) variable that raised the question of the impact of the intention variable, examining the perceived satisfaction of students, behavioral intent, and e-learning effectiveness [12][13][14]. This analysis, therefore, explores the satisfaction of learners, behavioral intentions, and the Blackboard e-learning system's effectiveness [12][13][14][15][16][17][18][19][20]. Using a standard questionnaire, a total of 424 university students were surveyed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors found a review in other studies related to the Intention (INT) variable that raised the question of the impact of the intention variable, examining the perceived satisfaction of students, behavioral intent, and e-learning effectiveness [12][13][14]. This analysis, therefore, explores the satisfaction of learners, behavioral intentions, and the Blackboard e-learning system's effectiveness [12][13][14][15][16][17][18][19][20]. Using a standard questionnaire, a total of 424 university students were surveyed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Linked to corporate disclosure and reputation is the way it is perceived by the consumer. In their paper, Neumann, Martinez, and Martinez (2020) explore sustainability efforts in the fast fashion industry, focusing on three dimensions: consumer perception, trust and purchase intention. Regarding the environment, the impact of distinct industries is not the same.…”
Section: Content Of the Special Issuementioning
confidence: 99%
“…The influence of such efforts on consumers’ decisions is not entirely clear yet. Neumann et al (2020) have tried to shed some light on this question by examining consumers’ attitudes toward two renowned brands regarding their pro-environmental efforts. Based on previous research, the authors developed a framework that depicts the relationships between perceptions of social responsibility, consumer attitude, trust, purchase intention and perceived consumer effectiveness and empirically tested the model with an internationally diverse sample of consumers.…”
Section: Content Of the Special Issuementioning
confidence: 99%
“…Purchase intention is the desire of an individual to purchase a product, based on their evaluation of the product (Grewal et al, 1998;Kang et al, 2013;Neumann et al, 2020;Wu & Chen, 2014). Intention to purchase goods is positively associated with the perceived value of the product (Grewal et al, 1998), with consumer's being more likely to repurchase goods they have experienced high satisfaction with (Mittal & Kamakura, 2001).…”
Section: Purchase Intentionmentioning
confidence: 99%
“…Purchase intention is defined as the desire of an individual to purchase a product, based on their evaluation of that product (Grewal et al, 1998;Kang et al, 2013;Neumann et al, 2020;Wu & Chen, 2014). This study adapted a three-item loyalty scale from Algesheimer et al, (2005), like the purchase intention scale used by Kang et al (2013).…”
Section: Purchase Intentionmentioning
confidence: 99%